2007
DOI: 10.1063/1.2437668
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of high- and low-resistance bistable states in polycrystalline NiO films

Abstract: The resistance switching current-voltage (I-V) characteristics in polycrystalline NiO films were investigated in the temperature range of 10K<T<300K. Very clear reversible resistive switching phenomena were observed in the entire temperature range. An analysis of the temperature dependence of the resistance switching transport revealed additional features, not reported in previous studies, that weak metallic conduction and correlated barrier polaron hopping coexist in the high-resistance off stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
116
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(124 citation statements)
references
References 15 publications
8
116
0
Order By: Relevance
“…Nickel oxide is a Mott-type insulator that exhibits electroresistive switching properties [9,11], often interpreted with a filamentary conduction model [20]. Our previous results on TMR single junctions in Ni/NiO/Co nanowires showed that filamentary conduction indeed occurred in those very small junctions [15].…”
mentioning
confidence: 94%
“…Nickel oxide is a Mott-type insulator that exhibits electroresistive switching properties [9,11], often interpreted with a filamentary conduction model [20]. Our previous results on TMR single junctions in Ni/NiO/Co nanowires showed that filamentary conduction indeed occurred in those very small junctions [15].…”
mentioning
confidence: 94%
“…There are at least three reported RS types: (i) unipolar memory RS [3][4][5][6][7][8][9][10][11][12], (ii) unipolar threshold RS [11][12][13], and (iii) bipolar memory RS [14][15][16][17][18] The latter process is usually controlled by setting a limit to the total amount of current flow, the compliance current (I comp ), to prevent a complete dielectric breakdown. As these two states are stable at V = 0, they can be used in a nonvolatile memory device.…”
mentioning
confidence: 99%
“…According to this model, charge transport consists of two parts: weak filamentary channels current (I f ) and the current in bulk (I i ). In this model, when the temperature is below 250 K, I f dominates in HRS 28 , however, in the present case, since the measurements were conducted at room temperature, current in HRS goes with the SCLC principle. Ultimately, the conduction behaviors in both the LRS and HRS also suggest that the high conductivity in on-state device should be a confined, filamentary effect rather than a homogenously distributed one, hinting that the active region where the actual phenomena happens is much smaller than the device size.…”
mentioning
confidence: 82%
“…In the negative voltage sweeping region, the behavior in LRS is similar to the positive voltage sweep region, however, the variation in the HRS is different. Such behavior in HRS region can be explained by a model called weak filamentary conduction channels 28 . According to this model, charge transport consists of two parts: weak filamentary channels current (I f ) and the current in bulk (I i ).…”
mentioning
confidence: 99%